PENGARUH AKSESIBILITAS TERHADAP KEPUASAN MASYARAKAT PADA SEKTOR PENDIDIKAN KABUPATEN KAMPAR PROVINSI RIAU - Sulaiman Alamsyah; Nico Pranata Mulya (ADMIN: Jurnal Administrasi Negara, 2024)
The aim of this research is to analyze the effect of accessibility on community satisfaction in the education sector in Kampar Kiri Hulu District. The research method used in this research is a quantitative method. The population in this study are heads of families who send their children to school and live in the territory of Kampar Kiri Hulu District. The total population is 3,386 heads of families and a sample of 358 heads of families. Researchers will obtain primary data in this research through questionnaires from people who have sent their children to school, websites, online journals, literature studies, and research-related references. Data collection techniques using observation, interviews and documentation. Data analysis techniques are descriptive analysis, multiple linear regression, classical assumption testing, hypothesis testing. Data was processed using SPSS 0.26. The results of the research show that accessibility has an effect on community satisfaction with the t-calculated value for the Accessibility variable being 5.563 with a positive regression coefficient value which shows that accessibility has a positive and significant effect on community satisfaction, and the Sig level. 0,000. If seen from the tcount value, it is greater than the ttable value (5.563 > 1.649) and the Sig value. 0.000 < 0.05.